Anorexia nervosa--diagnosis, aetiology, and treatment. Issue 842 (December 1995) - Hartman, D.
Abstract : The aetiology, assessment and treatment of anorexia nervosa are reviewed in the light of the classical accounts of Morton, Lasègue and Gull. The core symptoms are deliberate weight loss, disturbed body image and amenorrhoea, and complications may include cardiac failure, electrolyte disturbances, hypothermia and osteoporosis. Common clinical findings are described. Disturbed brain serotonin activity is implicated in the aetiology of anorexia nervosa, but there is little support for the use of pharmacological treatments. Psychological theories of aetiology are discussed with reference to Bruch, Crisp, Palazzoli and Minuchin: the common theme is the reaction of the patient and her family to the physical and social changes of puberty. Individual and/or family psychotherapy is seen as central to the treatment of anorexia nervosa, and the relevant clinical research is reviewed. The roles of general practitioners, general psychiatrists and eating disorder specialists are discussed in the light of recent consensus treatment guidelines.